2021
DOI: 10.21203/rs.3.rs-970723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost-Effectiveness of a Medication Event Monitoring System for Tuberculosis Management in Morocco

Abstract: Background Poor adherence to tuberculosis (TB) treatment can result in community transmission and drug resistance. Digital health technologies have been used to enhance adherence to TB medication for proper management, but the cost-effectiveness of this approach remains unclear.Methods We used the real data from the study conducted from April 2014 to December 2020 in Morocco to enhance the adherence to drug-susceptible TB treatment using a smart pillbox with a web-based medication monitoring system, called Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They consisted of eleven RCTs(14,15,24,1623), four cluster randomised control trials(2528), nineteen seventeen cohort studies(29,30,3947,31–38), one records reviews(48) and one quasi trial(49). All thirty-six had a control group and provided estimates of effect: Eleven evaluated community health care worker direct observation therapy (CHWDOT)(24,27,31,38)(14,19,25,26,29,33,39), nine evaluated family direct observation therapy (FDOT) (2123,28,37,40,41,48–50), five evaluated short Message Service reminders (SMS) (1518,51,52), six examined video observed therapy(VOT) (20,32,34,35,43,44) and five examined the electronic medication monitors (EMM) (30,42,4547) See Fig 2 . Substantive descriptions of the included studies including intervention evaluated can be seen in Table 2 and 3…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They consisted of eleven RCTs(14,15,24,1623), four cluster randomised control trials(2528), nineteen seventeen cohort studies(29,30,3947,31–38), one records reviews(48) and one quasi trial(49). All thirty-six had a control group and provided estimates of effect: Eleven evaluated community health care worker direct observation therapy (CHWDOT)(24,27,31,38)(14,19,25,26,29,33,39), nine evaluated family direct observation therapy (FDOT) (2123,28,37,40,41,48–50), five evaluated short Message Service reminders (SMS) (1518,51,52), six examined video observed therapy(VOT) (20,32,34,35,43,44) and five examined the electronic medication monitors (EMM) (30,42,4547) See Fig 2 . Substantive descriptions of the included studies including intervention evaluated can be seen in Table 2 and 3…”
Section: Resultsmentioning
confidence: 99%
“…(30) Another study conducted in Morocco evaluating the costs and cost-effectiveness of a Medication Event Monitoring System (using a smart pillbox with a web-based medication monitoring system)for Tuberculosis Management against standard of care (SoC) have shown the ICER of $434/DALY averted for managing drug-susceptible TB patients by MEMS relative to SoC thus MEMS is considered cost-effective in Morocco. (47)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the cost and cost-effectiveness of digital adherence technologies for tuberculosis treatment reported to date have not directly measured the amount of time spent by healthcare workers on adherence support and compared this time between a SoC and intervention arm, however the cost of staff care have been included [10][11][12]. These studies found DATs to be more expensive than SoC and with mixed evidence of treatment effect.…”
Section: Discussionmentioning
confidence: 99%